Maintenance of the EBV-specific CD8(+) TCRαβ repertoire in immunosuppressed lung transplant recipients - Nguyen, Thi HO (Immunol Cell Biol, 2017)
Epstein-Barr virus (EBV) is one of the most common viruses in humans, capable of causing life-threatening infections and cancers in immunocompromised individuals. Although CD8(+) T cells provide key protection against EBV, the persistence and dynamics of specific T-cell receptor (TCR) clones during immunosuppression in transplant patients is largely unknown. For the first time, we used a novel single-cell TCRαβ multiplex-nested reverse transcriptase PCR to dissect TCRαβ clonal diversity within GLCTLVAML (GLC)-specific CD8(+) T cells in healthy individuals and immunocompromised lung transplant recipients. The GLC peptide presented by HLA-A*02:01 is one of the most immunogenic T-cell targets from the EBV proteome. We found that the GLC-specific TCRαβ repertoire was heavily biased toward TRAV5 and encompassed five classes of public TCRαβs, suggesting that these clonotypes are preferentially utilized following infection. We identified that a common TRAV5 was diversely paired with different TRAJ and TRBV/TRBJ genes, in both immunocompetent and immunocompromised individuals, with an average of 12 different TCRαβ clonotypes/donor. Moreover, pre-transplant GLC-specific TCRαβ repertoires were relatively stable over 1 year post transplant under immunosuppression in the absence or presence of EBV reactivation. In addition, we provide the first evidence of early GLC-specific CD8(+) T cells at 87 days post transplant, which preceded clinical EBV detection at 242 days in an EBV-seronegative patient receiving a lung allograft from an EBV-seropositive donor. This was associated with a relatively stable TCRαβ repertoire after CD8(+) T-cell expansion. Our findings provide insights into the composition and temporal dynamics of the EBV-specific TCRαβ repertoire in immunocompromised transplant patients and suggest that the early detection of EBV-specific T cells might be a predictor of ensuing EBV blood viremia.